Biophysical Fitness Landscape of the SARS-CoV-2 Delta Variant Receptor Binding Domain. Issue 13 (15th July 2022) - Patrick, Casey; Upadhyay, Vaibhav; Lucas, Alexandra; Mallela, Krishna M.G.
Graphical abstract: Highlights: Delta variant RBD shows higher protein expression compared to the wild-type. Delta variant RBD does not affect ACE2 receptor binding affinity compared to the wild-type. Delta variant RBD does not escape Class 1 antibodies. Delta variant RBD escapes Class 2 and Class 3 antibodies. Fitness landscape of the Delta variant RBD is determined by the L452R mutation. Abstract: Among the five known SARS-CoV-2 variants of concern, Delta is the most virulent leading to severe symptoms and increased mortality among infected people. Our study seeks to examine how the biophysical parameters of the Delta variant correlate to the clinical observations. Receptor binding domain (RBD) is the first point of contact with the human host cells and is the immunodominant form of the spike protein. Delta variant RBD contains two novel mutations L452R and T478K. We examined the effect of single as well as the double mutations on RBD expression in human Expi293 cells, RBD stability using urea and thermal denaturation, and RBD binding to angiotensin converting enzyme 2 (ACE2) receptor and to neutralizing antibodies using isothermal titration calorimetry. Delta variant RBD showed significantly higher expression compared to the wild-type RBD, and the increased expression is due to L452R mutation. Despite their non-conservative nature, none of the mutations significantly affected RBD structure and stability. All mutants showed similar binding affinity to ACE2 and to Class 1 antibodies (CC12.1 and LY-CoV016) as that of the wild-type. Delta double mutant L452R/T478K showed no binding to Class 2 antibodies (P2B-2F6 and LY-CoV555) and a hundred-fold weaker binding to a Class 3 antibody (REGN10987), and the decreased antibody binding is determined by the L452R mutation. These results indicate that the immune escape from neutralizing antibodies, rather than increased receptor binding, is the main biophysical parameter that determined the fitness landscape of the Delta variant RBD.